An All‐Halogen Bonding Rotaxane for Selective Sensing of Halides in Aqueous Media1. Issue 43 (7th July 2014) - Mullaney, Benjamin R.; Thompson, Amber L.; Beer, Paul D.
Abstract The synthesis and anion binding properties of the first rotaxane host system to bind and sense anions purely through halogen bonding, is described. Through a combination of polarized iodotriazole and iodotriazolium halogen bond donors, a three‐dimensional cavity is created for anion binding. This rotaxane incorporates a luminescent rhenium(I) bipyridyl metal sensor motif within the macrocycle component, thus enabling optical study of the anion binding properties. The rotaxane topology was confirmed by single‐crystal X‐ray structural analysis, demonstrating halogen bonding between the electrophilic iodine atoms and chloride anions. In 50 % H2O/CH3CN solvent mixtures the rotaxane host exhibits strong binding affinity and selectivity for chloride, bromide, and iodide over a range of oxoanions.